If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -2) = (x + 3) Reorder the terms: 7(-2 + x) = (x + 3) (-2 * 7 + x * 7) = (x + 3) (-14 + 7x) = (x + 3) Reorder the terms: -14 + 7x = (3 + x) Remove parenthesis around (3 + x) -14 + 7x = 3 + x Solving -14 + 7x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -14 + 7x + -1x = 3 + x + -1x Combine like terms: 7x + -1x = 6x -14 + 6x = 3 + x + -1x Combine like terms: x + -1x = 0 -14 + 6x = 3 + 0 -14 + 6x = 3 Add '14' to each side of the equation. -14 + 14 + 6x = 3 + 14 Combine like terms: -14 + 14 = 0 0 + 6x = 3 + 14 6x = 3 + 14 Combine like terms: 3 + 14 = 17 6x = 17 Divide each side by '6'. x = 2.833333333 Simplifying x = 2.833333333
| 4x+8=20-7x | | 2y+15=3y-1 | | -90=6(7n-1) | | 23X-2=16X+51 | | 1x(3x-10)=90 | | y=0.5x+6.18 | | 5(x-11-7)=16 | | 5x+2+7x=180 | | 5+18=35 | | x=38+x | | 4p-13p+1p=-150 | | 60=3*2y+3*4 | | 2(x-5)-6x=-22 | | X+7=x+(-2) | | -59+x= | | 3z+5=3z+5 | | 9(x+5)=3(x-3)+6x | | 3z+5+6z+4=9z+9 | | x-59= | | 8r+3s=66 | | -8x-9=-3(x+3)-5x | | (x+2y)and(2x-3y)= | | 3X-3.9=-4.1 | | (x+5)(y-6000)=600000 | | 24=6*(x-7) | | logx^2=5 | | 2x^2+34x+17=0 | | 12n+9=6 | | (x+3)(x+4)+(x+6)(x-3)= | | 19=-(5x+7) | | 4(y-7)=5-(6y-2) | | C=39.45+0.25x |